A Comparison of High-Intensity Interval Training (HIIT) volumes on cognitive performance - Miller, M. G.; Hanson, N.; Tennyck, J.; Plantz, K. (Journal of Cognitive Enhancement, 2019)
The purpose of this study was to investigate the effect of two different acute bouts of high-intensity interval training (HIIT) on the Stroop Color Word task and Critical Flicker Fusion (CFF) threshold test. Twenty-five recreationally active subjects (12 men, 13 women; age 23 ± 2.79 years; body mass index 25.03 ± 3.15 kg m-2) were recruited for this study. The acute bouts of HIIT included low-volume (LV) and moderate-volume (MV) sessions. They each had a work to rest ratio of 1:1 min, and exercise was performed at 85% maximal heart rate. The LV session included five intervals, and the MV session included ten intervals. Prior to and after exercise, subjects completed the CFF test and Stroop task. Repeated measures ANOVAs were used to determine the effect of time and volume on test performance. CFF results showed a significant main effect for volume condition across pre/post trials (p = .006), with the MV having a higher average CFF threshold (37.73 ± .63 Hz) compared to LV (36.79 ± .68 Hz). Stroop results showed no main effect of volume condition or interaction (both p > .05) but revealed a significant main effect of time for mean reaction time (RT) total, mean RTcongruent/incongruent, and mean RTcontrol (all p < .001). There were no main effects of volume condition or time for proportion correct for all variables (p > .05). The results show that low- and moderate-volume HIIT have similar effects on post-exercise measures of executive function. Our results suggest that the volume of HIIT needed to elicit executive function performance gains may be lower than suggested in previous research.